2013
DOI: 10.4172/2155-6121.1000130
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Common Allergens in Allergic Rhinitis among the Patients Referred to the Allergy Clinic of Qods Hospital in Qazvin during 2007-2010

Abstract: This disease is sometimes mistakenly considered as a mild disease, while its symptoms may significantly affect patients' quality of life through causing fatigue, headache, cognitive disorder, effect on physiological health and other systemic symptoms. Allergic rhinitis is closely associated with the release of TH2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
(14 reference statements)
0
7
1
Order By: Relevance
“…Keeping cats as pets is popular in Iranian families and feral cats are abundant in the streets. The sensitization rate to cat hair in allergic individuals varied from 13-23.5% in several reports from Iran (33)(34)(35), which is higher than our result, likely due to differences in the study populations. In a study from Shiraz, 7% of the control group were sensitized to cat extract, which supports our finding (37).…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Keeping cats as pets is popular in Iranian families and feral cats are abundant in the streets. The sensitization rate to cat hair in allergic individuals varied from 13-23.5% in several reports from Iran (33)(34)(35), which is higher than our result, likely due to differences in the study populations. In a study from Shiraz, 7% of the control group were sensitized to cat extract, which supports our finding (37).…”
Section: Discussioncontrasting
confidence: 92%
“…A large variation in the rate of sensitivity to tree pollens was seen, possibly because of differences in the type and number of trees in each region, but most studies reported lower sensitization rates to tree than to grass and weed pollens. For example, in the Kerman study the rate of skin reaction to tree pollen was 2.5-9.6 percent among allergic patients (30), while in the Qazvin, Yasuj, and Ahwas the sensitivity rates among allergic patients were 26, 18, and 25-65%, respectively (34,35,31). Moghtaderi et al also reported a lower prevalence of tree than grass pollen allergy in allergy patients (33).…”
Section: Discussionmentioning
confidence: 99%
“…Which is similar to other Indian studies of Moitra et al [18] . When compared to our study pollens are the most common cause of sensitization in Tehran [19] , Tikrit [20] , Qazvin [21] . This difference also was expected since mites tend to require high humidity and moderate temperature to thrive, whereas pollens require a dry climate and a high temperature.…”
Section: Discussionmentioning
confidence: 89%
“…In Mediterranean and semi-arid regions, in accordance with the optimum 60% humidity and 25 °C temperature, a high prevalence of sensitivity to house dust mites (D. farina and D. pteronyssinus, particularly the latter) has been reported in several studies [7,27,[48][49][50][51]. This commonality may be due to the similar geographical characteristics of these regions.…”
Section: House Dust Mites and Other Arthropodsmentioning
confidence: 81%